Suburbia and rural landscapes in medieval Sicily - Castrorao Barba, Angelo, 1983-; Mandalà, Giuseppe, (Limina/limites. Archaeologies, histories, islands and borders in the Mediterranean (365-1556) ;, 2023)
This volume presents the results of the main ongoing archaeological and historical research focusing on medieval suburbia and rural sites in Sicily. It is divided into thematic areas: urbanscapes, suburbia, hinterlands; inland and mountainous landscapes; changes in rural settlement patterns; and defence and control of the territory.